Vulnerabilitäts- und Resilienzprofile städtischer Systeme. - Schulwitz, Martin (My University, 2020)
Die Arbeit hat zwei zentrale Ziele: Zum einen wird theoriebasiert ein Resilienzkonzept entwickelt, das den multidisziplinär geführten Resilienzdiskurs zusammenführt und gleichzeitig Ansatzpunkte für den Transfer in die Praxis bietet. Zum anderen wird die empirische Anwendung des Konzepts demonstriert und es werden, basierend auf den Ergebnissen, Vulnerabilitäts- und Resilienzprofile städtischer Systeme abgeleitet. Zur Erfüllung der ersten Zielsetzung wird der Stand der Forschung zur Resilienz aufgearbeitet und der Kontext erläutert, in dem das Resilienzkonzept im urbanen Raum seine Bedeutung erlangt. Es wird gezeigt, dass die zahlreichen vernetzten urbanen Systeme vielfältigen und ambivalenten Herausforderungen ausgesetzt sind, die auch in Zukunft zu Unsicherheit und Komplexität in der Planung führen werden. Die komplexen Vernetzungen städtischer Systeme liefern die Erklärung dafür, dass im Resilienzdiskurs ganzheitliche Betrachtungen des Systems Stadt anzustreben sind. Auf dieser Grundlage wird das Dimensionen Konzept urbaner Resilienz entwickelt, das urbane Resilienz aus den drei Dimensionen physischer Resilienz, institutioneller Resilienz und sozialer Resilienz konstruiert. Die Dimensionen spiegeln zentrale Definitionsstränge des Resilienzdiskurses wider, für die entsprechende Eigenschaften als Grundlage zur Operationalisierung aufgeführt werden. Zudem stehen die Dimensionen für diverse Teilsysteme auf unterschiedlichen Skalierungsebenen einer Stadt, in denen verschiedene Akteure tätig sind. Auf der Handlungsebene des Konzeptes werden den Dimensionen übergeordnete Zielsetzung als Ansatzpunkte für den Transfer des Konzeptes in die Governance- und Planungspraxis zugeordnet. Der empirische Teil demonstriert die Anwendung des Konzepts anhand der Analyse der Vulnerabilität städtischer Systeme als Gegenpol zur Robustheit, welche die zentrale Eigenschaft der physischen Dimension urbaner Resilienz darstellt. Für die Fallregion Reutlingen werden Hagelschäden an Gebäuden (Ereignis: Hagelsturm von Reutlingen 2013) untersucht und die Entwicklung eines fiktiven Abwassertarifs in unterschiedlichen Demografieszenarien modelliert.

This thesis at hand has two central objectives: On the one hand, a resilience concept is de-veloped, based on theory, which brings together the multidisciplinary resilience discourse and at the same time offers starting points for the transfer into practice. On the other hand, the empiri-cal application of the concept is demonstrated and, based on the results, vulnerability and resili-ence profiles of urban systems are derived. To meet the first objective, the state of research on resilience and the context in which the resili-ence concept attains its importance in urban areas are reviewed. It is shown that the numerous networked urban systems are exposed to diverse and ambivalent challenges, which will continue to lead to uncertainty and complexity in planning, in the future. The complex networking of urban systems provides the explanation that holistic considerations of the city as a system should be sought in the resilience discourse. On this basis, the dimension-concept of urban resilience is de-veloped, which constructs urban resilience from the three dimensions of physical resilience, insti-tutional resilience and social resilience. The dimensions reflect central strands of definition of the resilience discourse, for which corresponding properties are listed as the basis for operationaliza-tion. In addition, the dimensions stand for various subsystems on different scaling levels of a city, in which different actors are active. At the action level of the concept, overall objectives are as-signed as starting points for the transfer of the concept into governance and planning practice. The empirical part demonstrates the application of the concept based on the analysis of the vul-nerability of urban systems as a counterpoint to robustness, which represents the central property of the physical dimension of urban resilience. For the Reutlingen case study region, hail damage to buildings (event: hailstorm of Reutlingen 2013) is examined and the development of a fictitious wastewater tariff is modeled in different demographic scenarios. The selected challenges of cli-mate change and demographic change exemplarily reflect the diversity of the framing conditions to which cities are exposed. With the aim of being able to derive statements on the vulnerability and resilience of urban systems on the small-scale level, which is of particular importance for planning, comparable, ideal-typical building and usage structure types (BNT) are chosen as the level for analysis. The basis for this is the hypothesis that correlations can be determined between the spatial properties of the BNT and the susceptibility to hail damage or the sensitivity of the tar-iffs. Although the quantitative results show that there are no statistically meaningful correlations, a comparison of the measures of statistical location of the indicators shows the tendency for dif-ferences in the vulnerability of BNT. These tendencies are brought together as relational, qualita-tive vulnerability profiles of the BNT. In the conceptual part, the qualitative assessments of the vulnerability of the BNT are converted into assessments of the robustness and exemplary approaches are assigned to the BNT to con-struct the resilience profiles. Furthermore, general measures for the institutional and social di-mension of urban resilience are described, which can contribute to the implementation of the overarching objectives at the action level of the dimension concept. This provides concrete start-ing points for resilience mainstreaming in governance and planning practice.
Vulnerabilities and resilience profiles of urban systems.
Keywords: Stadtsystem; Urbaner Raum; Nachhaltigkeit; Ganzheitlichkeit; Resilienz; Vulnerabilität; Stresstest; Schadensvermeidung; Risikomanagement; Fallbeispiel; Wetterschaden; Empirische Untersuchung; Handlungsempfehlung; Abwasserbeseitigung; Abwasserkosten; Indikator; Soziale Resilienz; Naturgefahr